Selectivity of tembotrione + atrazine herbicides for grain sorghum - Ferreira Santos, Weverton; dos Santos Caldas, João Victor; Guerra da Silva, Alessandro; de Oliveira Procópio, Sergio; Braga Pereira Braz, Guilherme; Jakelaitis, Adriano (Revista Ceres, 2024)
The herbicide tembotrione may be seletivity to sorghum, which is of utmost importance in grain production systems. Thus, the present study aimed to evaluate the selectivity of tembotrione + atrazine combinations applied post-emergence at different phenological stages of grain sorghum. Four experiments were carried out in Rio Verde and Montividiu (state of Goiás) in succession to soybean cultivation in 2017 and 2018. The experiments were carried out in randomized block design with six replications, both in a (3x2) + 1 factorial arrangement. The first factor referred to three vegetative stages of application (V3, V5 and V7) associated with two doses of tembotrione (90 and 180 g ha-1) combined with atrazine (1,000 g ha-1) and and an additional treatment with no herbicide application. Tembotrione + atrazine applications at the V7 stage caused less damage to grain yield and dry mass accumulation in relation to V3 and V5. The dose of 90 g ha-1 tembotrione + atrazine combined with atrazine resulted in higher grain yields compared to 180 g ha-1, although still at lower levels compared to the treatment with no herbicides. Thus, herbicide tembotrione at doses of 90 and 180 g ha-1 combined with atrazine did not have selectivity for grain sorghum in applications at V3, V5 and V7 stages.